Renewable energy integration through optimal unit commitment and electricity storage in weak power networks - Nikolaidis, Pavlos; Chatzis, Sotirios P.; Poullikkas, Andreas (My University, 2019)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. In this work, the impact of intermittent renewable energy sources on total production cost is evaluated, using annual data regarding the isolated power system of the island of Cyprus. Once electrical energy storage (EES) is identified as an approach enhancing flexibility and reliability, the selected EES facilities are modelled and evaluated via a life-cycle cost analysis, based on the most realistic characteristics and cost metrics found in the literature. The results derived from the uncertainty analysis performed, show that vanadium-redox flow battery provides the highest net present value (NPV). However, sodium-sulfur battery system offers the most secure investment in terms of uncertainty range and mean value, followed by lead-acid battery system. Lithium-ion battery system exhibits expensive capital cost which still governs its overall cost performance achieving a negative mean NPV far below zero.
Keywords: EES facilities; Electrical energy storage; life-cycle cost analysis; uncertainty analysis; unit commitment; weak power networks